Natural heritage in Pałuki region, protection nad supervision of the Regional Director of Environment Protection in Bydgoszcz - Leszczyńska - Deja, Kornelia (Journal of Education, Health and Sport, 2017)
The purpose of this article is to present the most valuable natural advantages of the Pałuki region preserved in their natural or little changed state, and protected within nature reserves. The article presents role of the conservation plans for nature reserves. Additinally, it indicates records on Natura 2000.